2015
DOI: 10.1097/aog.0000000000001067
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Participation in Depression Care in Outpatient Perinatal Care Settings

Abstract: Objective To examine a wide range of study designs and outcomes to estimate the extent to which interventions in outpatient perinatal care settings are associated with an increase in the uptake of depression care. Data Sources PubMed, CINAHL, PsycINFO, ClinicalTrials.gov, and Scopus (EMBASE) were searched for studies published between 1999 and 2014 that evaluated mental health care use after screening for depression in perinatal care settings. Methods of Study Selection Inclusion criteria were: 1) English … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
91
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 140 publications
(105 citation statements)
references
References 30 publications
7
91
1
Order By: Relevance
“…60 Identifying effective engagement strategies is essential to optimizing the effectiveness of depression treatment. 61 Our study confirms that collaborative/integrated care, long shown to be effective in improving depression treatment and depressive symptoms in primary care settings, 9,[62][63][64][65]66,67,68 is an important complex, multilevel strategy for increasing treatment initiation. We also found some evidence that case management, another complex but patient-level strategy, may improve treatment initiation, similar to its effect on other health behaviors.…”
Section: Discussionsupporting
confidence: 77%
“…60 Identifying effective engagement strategies is essential to optimizing the effectiveness of depression treatment. 61 Our study confirms that collaborative/integrated care, long shown to be effective in improving depression treatment and depressive symptoms in primary care settings, 9,[62][63][64][65]66,67,68 is an important complex, multilevel strategy for increasing treatment initiation. We also found some evidence that case management, another complex but patient-level strategy, may improve treatment initiation, similar to its effect on other health behaviors.…”
Section: Discussionsupporting
confidence: 77%
“…It is estimated that only 15% of women with PPD symptoms seek professional care, leaving 85% of affected women untreated . Of those women who screen positive for PPD, it is estimated that only 22% follow up with professional mental health services . This leaves a critical gap between those women who suffer from PPD symptoms and those who receive treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Women with PPD face significant barriers to treatment, including a woman's fear of stigma and a lack of skilled professionals who can provide
specialized care . One systematic review found that, on average, only 22% of women who screened positive for PPD received at least one mental health visit . Therefore, awareness of risk factors for PPD may result in better monitoring and quicker treatment for at‐risk women.…”
Section: Introductionmentioning
confidence: 99%
“…19 One systematic review found that, on average, only 22% of women who screened positive for PPD received at least one mental health visit. 20 Therefore, awareness of risk factors for PPD may result in better monitoring and quicker treatment for at-risk women. A better understanding of the association between maternal history of child maltreatment and subsequent PPD can deepen women's health care providers' sensitivity to these issues and help further guide practice.…”
Section: Introductionmentioning
confidence: 99%